Los textos narrativos para mejorar la lectura en los niños - Palacios Castañeda, Dora Jacqueline (2021)
The work of professional sufficiency is entitled "Narrative texts to improve reading in children". Its objective is that through narrative texts and various teaching strategies, students can reach an outstanding level by understanding the text they read. The methodology used was to make predictions through the observation of what the text is about and predict the content, in order to directly imply the activation and use of previous knowledge. It was concluded that by applying narrative texts, not only academic processes but also aspects of life and daily life can be strengthened. Where, not only the child learns to decode or understand the explicit information in the text; but also to develop the ability to interpret texts and assume a position in front of them.